Salivary gland adenocarcinoma in a capuchin monkey (Sapajus nigritus) - Alessandra da Cruz; Crisan Smaniotto; Vinicius Dahm; Amália Ferronato; Manoela M. Piva; Nelson D. Lucas; Luana Canavessi; Laura F. de Noronha; Marilene M. Silva; Flávio S. Jojima; Aline M. Viott (Pesquisa Veterinária Brasileira)
ABSTRACT: Salivary gland neoplasms are infrequently documented in veterinary medicine and rare in non-human primates; therefore, they are scarce in the literature. Adenocarcinomas are malignant neoplasms that originate in the glandular epithelium and can affect various species. Our study presents detailed cytological, histological, and immunohistochemical findings of a salivary gland adenocarcinoma in a capuchin monkey (Sapajus nigritus). In the necropsy, a multilobulated mass was observed in the left submandibular region, characterized by a dark red surface, soft and firm upon cut surface. Histologically, a neoplastic proliferation of malignant epithelial cells was identified in the submandibular region and the lungs. The cells showed acinar formation, areas of architectural tissue differentiation loss, and solid aggregates. Immunohistochemistry was conducted to corroborate and elucidate the case. In the neoplasia, there was positive immunolabelling for pan-cytokeratin (Pan CK) and cytokeratin 7 (CK7), and negative labeling for thyroglobulin, thyroid transcription factor-1 (TTF-1), cytokeratin 20 (CK20), and Napsin A. The cytological, anatomopathological, and immunohistochemical findings lead to the diagnosis of salivary gland adenocarcinoma. Remarkably, this report seems to be the inaugural documentation of this neoplasm in a capuchin monkey (Sapajus nigritus).